Cognitive Study Strategies and Motivational Orientations among University Students: A Latent Profile Analysis - Conny De Vincenzo; Matteo Carpi (MDPI AG, 2024)
Cognitive study strategies and motivational orientations play a crucial role in promoting successful learning and academic achievement. This study aims to explore the presence of different cognitive-motivational profiles among Italian university students using latent profile analysis. A sample of 476 university students (mean age: 26.5 ± 9.6 years; 71.6% female) participated in a cross-sectional online survey, including the Self-Regulated Knowledge Scale-University, the Academic Motivation Scale, the Students' Self-Efficacy Scale, the Outcome Questionnaire-45, and a brief measure of dropout intention. Latent profile analysis identified three distinct configurations of self-regulated learning strategies and motivational orientations: "autonomous-motivated deep learners" (AUT-Learn; 60.5%), "externally-motivated balanced strategists" (EXT-Bal; 36.8%), and "externally-motivated task performers" (EXT-Task; 6.8%). The three profiles exhibit significant differences in self-efficacy, dropout intention, grade point average (GPA), and psychological wellbeing. The AUT-Learn profile showed higher self-efficacy than EXT-Bal and EXT-Task, and higher GPA than EXT-Task. Additionally, AUT-Learn participants reported lower dropout intention and higher psychological wellbeing compared to EXT-Bal and EXT-Task, while EXT-Bal showed lower dropout intention and better wellbeing than EXT-Task. The predictive validity and practical implications of this classification warrant further investigation in dedicated longitudinal studies.